Implementasi Sistem Pendeteksi Rogue Access Point Dengan Metode Perhitungan Nilai Round Trip Time - Fahmi Syahrulah; Adhitya Bhawiyuga; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
With the increasing development of wireless technology, which provoke the cyberattack using wireless technology increase as well, this would make user data be put to risk. One of the cyberattack that exploit wireless technology is Rogue Access Point. To prevent this, RAP detection system was made with comparing round trip time method. This system sent a DNS lookup to get round trip time. RAP would return much longer round trip time value than the legitimate access point, this happen because the added hop that was passed during the trip to RAP. To minimalize the impact from unstable network that would affect the accuracy of detection system, filtering mechanism is used to filter round trip time value that is deemed as an anomaly. Testing will be done to the two similar access point which one of them is the RAP. Round trip time value from both access point will be compared, which will be used as parameter to determine RAP. In this research the accuracy detection would be never less than 90%.